Cambios En La Coordinación Dinámica General Con La Aplicación De Un Programa De Juegos Predeportivos En Niños De 10 A 12 Años De La Escuela De Fútbol Independiente H. A. O. M. DE Circasia Quindío (2016)
This research aimed to identify changes in the general dynamic coordination with the implementation of a program of sport games in children 10 to 12 years old of school football independent H. A. O. M. of Circasia, Quindío. The methodology used was of the month type without control group, with quantitative approach, took into account a population of 16 children with an average age of 11,31 (0.79 ±) years old of school football independent H. A. O. M. of Circasia, Quindío, these were operated with the program of sport games which comprised 36 sessions applied 3 times per week , with a duration of 1 hour and that they were members of sports such as volleyball, basketball and handball, the Group was assessed by the test of the zigzag at the beginning and at the end of the program. The average values obtained in the pretest and posttest were 13.47 (1.66 ±) and 11.5 (± 1.58) seconds respectively, presenting a significant difference between both values (P = 0.000). The conclusion which was reached is that a games sport program that integrates the volleyball, basketball and handball developed with a frequency of 3 days a week and with duration of 1 hour general in 10-12 years old, produces significant changes in dynamic coordinating practitioners of soccer.